Cardiac manifestations of Anderson-Fabry disease in heterozygous females - Kampmann, Christoph; Baehner, Frank; Whybra-Trümpler, Catharina; Martin, Claudia; Wiethoff, Christiane Maria; Ries, Markus; Gal, Andreas; Beck, Michael (Journal of the American College of Cardiology, 2002)
Objectives - We sought to define the prevalence of cardiac involvement in female patients with Anderson-Fabry disease (AFD). - Background - Anderson-Fabry disease is a rare inborn X-linked lysosomal storage disorder. Globotriaosylceramide (Gb3), the major substrate of the deficient α-galactosidase A enzyme, accumulates progressively in vulnerable cells, including the cardiovascular system. It has been believed that heterozygous females have less cardiac involvement than hemizygous males with AFD. - Methods - We performed two-dimensional echocardiographic examinations of female patients heterozygous for AFD. - Results - Since 1997, a total of 55 female patients (mean age, 39.6 years; range, 6.1 to 70.8 years) with proven AFD have been investigated prospectively at our hospital. Of these, 13 (23.6%) had normal left ventricular (LV) geometry and LV mass (LVM). Seven patients (12.7%) had concentric remodeling, 29 patients (52.7%) concentric LV hypertrophy (LVH), and 6 patients (10.9%) eccentric LVH (2 with subaortic pressure gradients). There was a strong correlation between age and the severity of LVH (r2= 0.905; p < 0.0001), and all patients older than 45 years had LVH. With increasing LVM, there was a significant age-independent decrease in systolic and diastolic LV function. Mild thickening of the aortic valve leaflets was present in 25.5% of patients, with the same percentage demonstrating mild thickening of the mitral valve leaflets. Mild mitral valve prolapse was documented in 10.9% of patients. - Conclusions - Cardiac involvement, with LVH and structural valve abnormalities, is very common and worsens with age in females who are heterozygous for AFD, and they should therefore be considered candidates for enzyme replacement therapy.
Gesehen am 16.05.2019